Kriterien und Quantifizierung von fibröser Dysplasie beim MDP-Scanning - Sathekge, M. M.; Clauss, R. P. (Nuklearmedizin - NuclearMedicine, 1995)
Eleven patients with histologically proven fibrous dysplasia (biopsy) were imaged with 3-phase bone scanning, using 99mTc-MDP. Ten had monostotic and one had polyostotic fibrous dysplasia. The perfusion (phase I) and uptake (phase III) of monostotic lesions was compared to the normal contralateral side and the rest of the skeleton was inspected for other abnormalities. Lesions presented with slightly increased perfusion (1.65 normal ± 0.907) and markedly increased uptake of tracer (6.0 normal ± 2.58). Other features that were noted are high spinal and scapula and poor renal tracer uptake.
Keywords: Fibrous dysplasia; nuclear medicine; 99mTc-MDP